Analisis Perbedaan Pendapatan Rumah Tangga Peternak dan Bukan Peternak Kambing di Kota Kendari - Rosmawaty, Rosmawaty (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2011)
The research objectives were to know: Different incomes among households who effort and non-effort of goats husbandry in Kendari city. This research was conducted in Kendari City, from August through September 2009 with samples determined Random Sampling each other 30 persons of the stockman and purposively to non-stockman. Data were collected from the director of the interview and analyzed with analysis of financial feasibility analysis and test-T. Results of this research were showed that: there was various real (significance) between household income who effort and non-effort goats in Kendari city. It was based on test-T, where a value of t-hit 2,216 more than t-table 1,671.